Role of bank competition in determining liquidity creation: Evidence from GCC countries - Shoaib Ali; Imran Yousaf; Sumayya Chughtai; Syed Zulfiqar Ali Shah (Journal of Applied Economics, 2022)
This study aims to investigate the impact of banking-sector concentration on the banks' liquidity creation in GCC countries over the period from 2012 to 2018 by using a dynamic GMM panel procedure. The results suggest that increased bank competition reduces banks' liquidity creation across the GCC countries. The study's findings are in line with the 'financial fragility hypothesis" according to which banks to reduce their lending activities when competition is high in the market. The evidence suggests that the banking industry is different from others, and pro-competitive policies in the banking industry can reduce liquidity provision by banks. In the context of policy implications, a concentrated banking system discourages capital provision to firms; hence, regulators have to take appropriate measures to resolve the problem of a reduced supply of capital. Government must regulate the banking sector by keeping in view their long-run goal as competition is a double-edged sword in banking.
Keywords: 330; Concentration; Financial Fragility hypothesis; GCC; Liquidity creation